Efficiency of rapid sand filtration by using Dual-Layer filter for filtering wastewater from Salamiah treatment station in Syria: دراسة كفاءة المرشحات الرملية السريعة باستخدام مرشح ثنائي الطبقة لفلترة مياه الصرف الصحي الناتجة عن محطة معالجة سلمية في سورية - Abdul kafi Mohammad Shmit, Naeima Ajib, Mahmoud Alfattamah (Journal of engineering sciences and information technology, 2021)
Water exiting from treatment stations, which work by the fixing manner in natural oxidization ponds, has a high concentration of solid substances due to the existence of the algae, and for reusing this water for agriculture these substances must be reduced.The subject of this research is to study the efficiency of one of the rapid filtration forms, using dual-layer rapid filters, in order to get rid of the solid particles suspended in the final output water of Salamiah Sewage Treatment Plant. To achieve this, an experimental treatment station was constructed and operated to evaluate the efficiency of wastewater treatment by using a rapid sand filter, with a filter bed composed of local sand with pistachio peels, the total filter bed height (1.4m) consisting of (1m) sand and (40 cm) pistachio peels. The action of the experimental filter has been compared over three cycles of filtration and the optimum filtration cycle has been reached at a plenty rate of 12 m3/m2.h, where the efficiency of removing the turbidity, TSS and COD was 32.43%, 89.79% and 64.29% respectively.It is discerned that these filters are easy to be invested and has a high output in comparison with filtrating by the general traditional way, and it is recommended for use in treatment stations operating with the natural oxidization ponds method.